Fast-track Cardiac Surgery in Children: Feasibility in Bangladeshi Setting - Quader, SA; Sarker, R; Ahmed, F; Hasan, MK; Beg, AK; Salam, ABMA; Ahmed, NU (Cardiovascular Journal, 2010)
Background: Fast-track recovery protocols in cardiac surgery is gaining worldwide popularity and have contributed to significant reductions in the postoperative hospital stay and cost without any increase in postoperative mortality and morbidity. The aim of this study was to find out the feasibility of fast track paediatric cardiac surgery in Bangladeshi setting. Method: It was a prospective study conducted in National Institute of Cardio-vascular Diseases, Dhaka, from July 2009 to June 2010. All patients, between 3 to 18 years, underwent surgical closure of atrial or ventricular septal defect under cardio-pulmonary bypass. 20 patients from our unit served as fast track group and 30 patients from other units of the same hospital served as conventional group. Fast track patients were extubated in less than 6 hours after surgery, shifted from ICU in less than 24 hours and geared up to discharge home within 3 days of surgery. Result: 18 (90%) of the 20 patient of the fast track group were discharged within 3 days of surgery, 2 patients cannot be discharged within this time frame. Mean post operative hospital stay for study group was 3.1 days, whereas the mean hospital stay in the control group was 7.5 days. Follow-up was 100% complete at 30 days. There was no major in-hospital or out-of-hospital complications in either group. No patient was readmitted at our centre or elsewhere for any complication arising from this process. Conclusion: Fast tracking is feasible and safe in low-risk paediatric open-heart surgery in Bangladeshi scenario. A multidisciplinary approach with a set protocol is required to achieve this goal in a safe and reproducible manner. Keywords: Cardiac surgery; Congenital heart disease; Fast track; Hospital discharge. DOI: 10.3329/cardio.v3i1.6427 Cardiovasc. j. 2010; 3(1): 50-54